(untitled) (Вісник: Міжнародні відносини, 2025)
Background. This article examines one of the key challenges Ukraine faces on its path toward NATO membership: the existence of temporarily occupied territories. The relevance of the topic stems from the fact that territorial conflicts present a serious obstacle to Euro-Atlantic integration. The aim of the study is to analyze the legal, political, and security aspects of Ukraine’s accession to the Alliance under the condition of partial occupation of its territory, to explore relevant historical precedents, and to propose possible scenarios for further developments. M e t h o d s. The research employs comparative-historical, analytical, and normative legal methods. It analyzes official NATO documents, international legal frameworks, the positions of political leaders and experts, as well as precedents of other countries joining the Alliance with unresolved territorial disputes. R e s u l t s. The study shows that the Alliance has previously admitted countries with territorial disputes (e.g., West Germany, Estonia, Croatia), which provides grounds for developing new approaches to Ukraine’s accession. Two primary scenarios are justified: the “West German model,” under which membership would apply only to non-occupied territories, and the option of amending Article 6 of the North Atlantic Treaty. Each scenario carries both potential benefits and significant risks for sovereignty, national security, and the unity of Ukrainian society. C o n c l u s i o n s. Ukraine should continue its active integration with NATO while insisting on the recognition of its entire territory within internationally recognized borders. Temporary solutions must not contradict the long-term goal of full de-occupation. Accession to the Alliance is not only an element of defense strategy but also a means of ensuring stability in Europe.